Characteristics of Generation (Z) and the most important psychological and social problems in UAE society: An Analytical study - Setti, Chaimae; Abou Elkheir, Omaima (Al-Adab Journal, 2024)
The current research dealt with the topic "Characteristics of Generation Z and its most important psychosocial problems in UAE society", which, in the view of many researchers, is a worthwhile topic and offers an in-depth understanding of what Generation Z is, its characteristics and the imbalances affecting social construction, it reveals the growing value collision of the Generation Z and its versatility , in addition to being subject to a situation of double standards, due to the effects of the digital virtual world, which has provided countless outlets of interaction and interchange between multiple cultures. However, due to this unconditional openness to the outside world and other civilisations without the existence of rules or values guiding this liberty has shown us that it may result in a number of psychosocial and social issues among the Z generation, the most prominent of which are: -Isolation and hesitation about participating in society, overthinking, and worrying about the future, emotional fragility, as well as depression caused by an absence of real-life relationships and conflicts with oneself. Moreover, mental distraction as a result of adhering to ideals imposed on them as well as the stipulates of the values and contents of digital media. Furthermore, the existence of behaviours that society and families reject as being outside the norm and what is socially recognised, which may lead to conflict between generation Z and the generation of parents, also making comparisons between themselves and what celebrities and influencers set and own in digital applications and finally, moral degeneration against absolute freedom and lack of supervision. Searching try to understanding the need to create a different interpretation of numerical and its effects on Generation Z by digital sociologists and looking at modern standards to recognise the interrelationships between them and segments and phenomena of society, i.e., the ways in which Generation Z is treated in the digital space. In addition, the search confirms that the role of social establishment as an educational institution should be activated in the process of preparing, supporting, and embracing the members of Generation Z by enhancing their awareness of the reality, shaping their personality, developing their abilities and knowledge, and enriching their culture.